RESPON KONSUMEN TERHADAP IKLAN MIE SEDAP - Susanta Susanta (Jurnal Ilmu Komunikasi, 2008)
The aims of the research are identify Mie Sedaap advertising strength, customer’s re- sponse strength, customer’s response index, and relationship between advertising strength and customer’s response strength. Closed questionnaire is use to collect data from 100 respondents. Purposive sampling technique used to determine respondent. Date tabulating is kind of descriptive analysis that is used to analysis advertising strength, customers’ response strength, and customers’ response index. Rank Spearman correlation use to analysis relationship between advertising strength and customers’response strength. The result of descriptive analysis show that strength of Mie Sedaap advertising Titi Kamal Version is in the average category. It means the respondent see the advertising very often but there’s no special thing on the interest build. With the hierarchy effect model, it shows the con- sumer respondent has goes outside awareness, interest, desire, convict, and purchase level. Most of the respondents do the purchase, while some respondent didn’t purchase just because they didn’t get convicted about what the advertising claim and didn’t get interest whit that. Mie Sedaap advertising can be categorized success because most of the people buy the goods. But if we look to the strength of the advertising which created only weak responses, there’s no guaran- tee they will buy again in the future or continuing the purchase. In the other hand, for those who haven’t bought the product, still very small possibility to buy. It is because the weak support from the advertising. The result of correlation analysis also shows relations between strength of the advertising and strength of consumer response is significant on level á = 0.05. If the company wants to get the goal of from the advertising, they have to repair the advertising so it can improve the awareness, interest, desire, conviction and purchase level.